A method for optodynamic characterization of Erbium laser ablation using piezoelectric detection - Bosiger, Georgije (Strojniški vestnik, 2014)
The paper presents a new method for characterization of Erbium laser ablation processes widely employed in various medical applications. The method is based on detection of shock waves propagating in air above the irradiated surface by means of a wideband piezoelectric sensor and analysis of the acquired signal waveforms. This sensor set-up offers the possibility for integration into an Er:YAG laser hand-piece, which opens the way to on-line process monitoring. A new model of the sensor is developed in order to take into account the relative position and orientation of the sensor and its mechanical and electrical properties. The model is verified by comparing the signal waveforms acquired at different sensor distances and orientations relative to the ablated spot with the theoretical waveforms calculated on the basis of numerical solutions of the Taylor-Sedov point explosion model and the developed sensor model. Excellent agreement is observed between the acquired and theoretical waveforms, which serves as a basis for a novel method that employs shock-wave energy released during the ablation process as a process characteristic that can be determined from the acquired signal waveforms. It is shown that shock-wave energy exhibits significantly less dependence on the position and orientation of the sensor than other waveform characteristics (time of fight, amplitude, etc.) that are currently used for the ablation process characterization.
Keywords: erbijev laser; laserska ablacija; piezoelektrična detekcija; točkasta eksplozija; udarni valovi